Semantic Error Analysis in English Oral Presentation - Pramesti, Rahmadini Windy; Putra, Aidil Syah; Iffah, Ida Farhatul; Sarrohmahniyati, Sarrohmahniyati (Dinamika Bahasa dan Budaya, 2024)
This study aims to analyze the oral semantic errors made by students during their English oral presentations and to classify these errors according to the categories defined by Al-Shormani and Al-Sohbani's (2012), adapted from James' (1998) error classification theory. This study uses qualitative descriptive analysis method. The study’s population consisted of approximately 50 6th-semester English Education students at Universitas Muhammadiyah Tangerang, with a sample size of 14 students from class 6A1, who were scheduled to perform their oral presentation. The data collection techniques used are observation and documentation. Data analysis involves several steps: identifying semantic errors, categorizing the collected semantic error, describing the corrected versions of these semantic errors, and concluding with a descriptive analysis of the semantic errors. The findings of this study found that among the fifteen semantic errors found in students’ oral presentations, lexical choice errors were the most frequent, totaling 8 errors (53%). Collocation and formal misformation had the lowest occurrence, each with only 1 error (7%). Additionally, lexical-grammatical choice errors accounted for 3 instances (20%), while formal misselection accounted for 2 errors (13%) in the study. Keywords: oral presentation, semantic, semantic error